Analysis of scapular kinematics during active and passive arm elevation - Kai, Yoshihiro (J Phys Ther Sci, 2016)
[Purpose] Early postoperative passive motion exercise after arthroscopic rotator cuff repair remains controversial. To better understand this issue, this study was aimed at evaluating scapular kinematics and muscle activities during passive arm elevation in healthy subjects. [Subjects and Methods] The dominant shoulders of 27 healthy subjects were examined. Electromagnetic sensors attached to the scapula, thorax, and humerus were used to determine three-dimensional scapular kinematics during active arm elevation with or without external loads and passive arm elevation. Simultaneously, the activities of seven shoulder muscles were recorded with surface and intramuscular fine-wire electrodes. [Results] Compared with active arm elevation, passive elevation between 30° and 100° significantly decreased the scapular upward rotation and increased the glenohumeral elevation angle. However, no significant differences in scapular posterior tilt and external rotation were observed between active and passive arm elevation, and scapular plane kinematics were not affected by muscle activity. [Conclusion] Unlike active motion with or without an external load, passive arm elevation significantly decreased the scapular upward rotation and significantly increased the mid-range glenohumeral elevation. These data, which suggest that passive arm elevation should be avoided during the early postoperative period, may expand the understanding of rehabilitation after arthroscopic rotator cuff repair.